PENGATURAN PENGGUNAAN ALAT TANGKAP PERIKANAN MENURUT UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERUBAHAN UNDANG-UNDANG NOMOR 31 TAHUN 2004 TENTANG PERIKANAN - Noprianto, Wahyu; Haryono, Dodi; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Geographical condition of Indonesia as a country that two-thirds of marine waters is composed of marine coastal seas, sea bays and straits give Indonesia the abundant riches, in terms of want to keep and preserve natural resources and biodiversity. The presence of trawls directly proportional to the needs of the community, but its use was then impact on the environment. Indonesian government in this case still happened the tug interests related regulations on fishing gear, especially related to the use of trawls.Based on this understanding, the authors of this paper formulated the two formulation of the problem, namely: first, how setting fishing gear fishery based on Law Number 45 Year 2009 on the Amendment of Law No. 31 Year 2004 on fisheries? second, what are the weaknesses setting fishing gear fisheries in Indonesia?The research method in this study, first, this kind of research is legal juridical research because in this study the authors do a review of literature, both include print media, books, literature, and electronic media.From the research, there are three main things that can be inferred. First, Regulating the use of fishing gear fishery according to Law No. 45 Year 2009 on the Amendment of Law No. 31 of 2004 on Fisheries does not clearly contains a provision concerning the use of fishing gear fisheries in Indonesia. Second, weakness Fisheries Law Indonesia in setting fishing gear in IndonesiaFirst author's suggestion should be the perception among all stakeholders and the public to determine the attitude of how best to use fishing gear trawls arrangements applied in Indonesia and expected government to be able to realize the policies that have been made consistently and responsibly with the various stakeholders in the field of fisheries in Indonesia.Second, to get clarity related to setting fishing gear trawls in Indonesia it is expected the government to synchronize the substance of the legislation in the field of fisheries and integrated appropriately so there is no conflict between the rules with each other in the same set.Keywords : Trawls – Environment – Biodiversity